The Influence of Profitability, Liquidity, Assets Structure, Company Size and Risk on Capital Structure: Study on Food and Beverage Companies on Indonesia Stock Exchange - Rosdiana, Riska; Karyatun , Subur; Sari, Christina Ariadne Sekar (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This research aims to determine the effect of profitability, liquidity, tangibility, firm size, and risk on capital structure. The population used in this study is manufacturing corporation sub-sectors of food and beverages listed on the Indonesia Stock Exchange 2014-2018 period. This research used a saturation sampling method and acquired a sample of 16 companies. Independent variables use this research of profitability, liquidity, tangibility, firm size, and risk, and dependent variables use capital structure. Hypothesis testing was done by using double linear regression by Eviews 9. The results of this research show that (1) profitability has a positive and significant effect on capital structure, (2) liquidity has a positive and not significant effect on capital structure, (3) tangibility and firm size have a negative and not significant effect on capital structure, (4) risk has a positive and not significant effect on capital structure